2016
DOI: 10.3892/etm.2016.3295
|View full text |Cite
|
Sign up to set email alerts
|

Detection and genotype analysis of AmpC β-lactamase in Klebsiella pneumoniae from tertiary hospitals

Abstract: Abstract. The aim of the present study was to investigate the phenotype and genotype of plasmid-mediated AmpC (pAmpC) β-lactamase in Klebsiella pneumoniae and its antibiotic resistance. A total of 130 non-repetitive clinical isolates of Klebsiella pneumoniae, obtained from tertiary hospitals, were phenotypically screened for pAmpC β-lactamase production with the cefoxitin disk diffusion test. β-lactamase genes in the screened isolates were detected using multiplex polymerase chain reaction (PCR); carbapenemase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
4
7
0
1
Order By: Relevance
“…Moreover, the rate of positive detection of AmpC type β-lactamase was 14%, with only the DHA type being detected. DHA has been reported as the most frequent among AmpC β-lactamase-producing KP isolates in many studies ( Shi et al, 2013 ; Liu and Liu, 2016 ), which was in line with our study. Therefore, DHA is speculated to be the most common type of AmpC β-lactamase in China.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the rate of positive detection of AmpC type β-lactamase was 14%, with only the DHA type being detected. DHA has been reported as the most frequent among AmpC β-lactamase-producing KP isolates in many studies ( Shi et al, 2013 ; Liu and Liu, 2016 ), which was in line with our study. Therefore, DHA is speculated to be the most common type of AmpC β-lactamase in China.…”
Section: Discussionsupporting
confidence: 93%
“…A limited number of antibiotic treatment options are available in infections caused by AmpC-producing K. pneumoniae. Carbapenems have emerged as a primary agent for management of infections due to AmpCproducing K. pneumoniae [9]. However, it has been reported that AmpC betalactamase can increase the MIC value of carbapenems and confer resistance to this class of antibiotics [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to resistance to penicillins and most cephalosporins, unlike ESBLs, AmpC-producing organisms can degrade cephamycins [8]. AmpC beta-lactamase-producing organisms show more extensive antibiotic resistance features in comparison with other ESBLs-producing organisms [9]. It has been reported that AmpC beta-lactamase can confer resistance to cefepime (fourth-generation cephalosporin antibiotic) and also can increase the minimum inhibitory concentration (MIC) value of carbapenems [9,10].…”
Section: Introductionmentioning
confidence: 99%
“… 10 Multi-drug resistant K. pneumoniae , which is one of the major reason for nosocomial infections, poses a serious threat in the clinical practice because of the difficulties in the diagnosis due to the production of Carbapenemase and ESBLs/AmpC enzymes. 11 …”
Section: Introductionmentioning
confidence: 99%